Cardiac Resuscitation Events: One Eyewitness Is Not Enough*. Issue 4 (May 2015) - Su, Lillian; Waller, Mary; Kaplan, Seth; Watson, Anne; Jones, Melissa; Wessel, David L.
Abstract : Objective: To determine the accuracy of paper cardiopulmonary resuscitation records. Design: Case series. Setting: Twenty-six-bed video-monitored pediatric cardiac ICU. Patients: All patients who had a resuscitation event with available video and electronically stored vital sign and waveform data from May 2012 to February 2013. Interventions: None. Measurements and Main Results: There were 41 cardiopulmonary resuscitation events during the study period. Fifteen had complete and valid data from the paper cardiopulmonary resuscitation forms, the retrieved monitor data, and the continuous bedside video monitoring. These 15 events occurred in 12 individual patients, and there was 100% agreement of data in the documentation of interventions in place (ventilation, arterial catheter, pulse oximetry, and vascular access) and in the presence of a witness at the onset of the arrest. All events were witnessed. Of the 15 events, video and monitor review revealed that 14 used waveform and numeric capnometry to confirm endotracheal tube/tracheostomy placement, but this section was only completed on the paper cardiopulmonary resuscitation record in three of the 14 cases. All records showed no discrepancies in the time of return of spontaneous circulation. The video and monitor review revealed delay in initiating cardiopulmonary resuscitation (mode, 2 min; two cases ≥ 7 min) and shockable rhythms (ventricular arrhythmia) in two cases. A sign of pulseless state was discovered in seven cases classified on the paper record as "always with a pulse." Those include sudden loss of consciousness, flat arterial line tracing, and abrupt drop in the partial pressure of exhaled carbon dioxide tracing (< 10 mm Hg). Conclusions: Eyewitness accounts of cardiopulmonary resuscitation are often inaccurate and incomplete. Review of information from video and electronically stored vital sign and waveform data provides more accurate information than review of paper-based cardiopulmonary resuscitation records and may provide the insight necessary to improving cardiopulmonary resuscitation.